Improved Ultrafast Power Doppler Imaging using United Spatial-Angular Adaptive Scaling Wiener Postfilter - Wang, Yadan; Huang, Lijie; Wang, Rui; Wei, Xingyue; Zheng, Chichao; Peng, Hu; Luo, Jianwen (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2023)
Ultrafast power Doppler imaging (uPDI) using high-frame-rate plane-wave transmission is a new microvascular imaging modality that offers high Doppler sensitivity. However, due to the unfocused transmission of plane waves, the echo signal is subject to interference from noise and clutter, resulting in a low signal-to-noise ratio and poor image quality. Adaptive beamforming techniques are effective in suppressing noise and clutter for improved image quality. In this study, an adaptive beamformer based on a united spatial-angular adaptive scaling Wiener postfilter (uSA-ASW) is proposed to improve the resolution and contrast of uPDI. In the proposed method, the signal power and noise power of the Wiener postfilter are estimated by uniting spatial and angular signals, and a united generalized coherence factor (GCF) is introduced to dynamically adjust the noise power estimation and enhance the robustness of the method. Simulation and in vivo data were used to verify the effectiveness of the proposed method. The results show that uSA-ASW can achieve higher resolution and significant improvements in image contrast and background noise suppression compared to conventional delay-and-sum (DAS), coherence factor (CF), spatial angular coherence factor (SACF), and adaptive scaling Wiener (ASW) postfilter methods. In the simulations, uSA-ASW improves contrast-to-noise ratio (CNR) by 34.7 dB (117.3%) compared to DAS, while reducing background noise power (BNP) by 52 dB (221.4%). The uSA-ASW method provides FWHM reductions of 301 μm (59.5%) and 568 μm (56.9%), CNR improvements of 25.6 dB (199.9%) and 42 dB (253%) and BNP reductions of 46.1 dB (319.3%) and 12.9 dB (289.1%) over DAS in the experiments of contrast-free human neonatal brain and contrast-free human liver, respectively. In the contrast-free experiments, uSA-ASW effectively balances the performance of noise and clutter suppression and enhanced microvascular visualization. Overall, the proposed method has the potential to become a reliable microvascular imaging technique for aiding in more accurate diagnosis and detection of vascular-related diseases in clinical contexts.